Cannabis use disorder among people using cannabis daily/almost daily in the United States, 2002–2016 - Santaella-Tenorio, Julian (Drug Alcohol Depend, 2019)
BACKGROUND: Cannabis use disorder (CUD) prevalence among people reporting past-year cannabis use declined from 2002-2016. We examined whether similar reductions in CUD were observed among people reporting daily/almost daily cannabis use. We expected that CUD prevalence among people reporting daily/almost daily use would not decrease. METHODS: We used 2002-2016 National Survey on Drug Use and Health (NSDUH) data, including 22,651 individuals using cannabis 300+ days in the past year. CUD was defined using DSM-IV criteria for cannabis abuse and/or dependence. Age categories included: 12-17, 18-25, and 26+. Annual prevalence of CUD, cannabis dependence, cannabis abuse, and each individual abuse/dependence items accounted for the complex survey design. Differences in trends over time were examined by age group. RESULTS: From 2002-2016, the prevalence of CUD among people reporting daily/almost daily cannabis use decreased by 26.8% in adolescents, by 29.7% in ages 18-25, and by 37.5% in ages 26+. Prevalence of DSM-IV cannabis dependence decreased significantly among adolescents (−43.9%) and young adults (−26.8%) but remained stable in adults 26+. Reductions in most dependence items were observed in young adults, with less consistent patterns in adolescents and adults 26+. Prevalence of DSM-IV cannabis abuse decreased overall and for each abuse item across all age groups. CONCLUSIONS: Contrary to expectations, CUD prevalence decreased significantly across all ages reporting daily/almost daily cannabis use between 2002-2016. Cannabis dependence prevalence decreased for adolescents and young adults and was stable only among adults ages 26+ reporting daily/almost daily cannabis use. Potential drivers of this decrease should be further explored.